Measuring endogenous changes in serotonergic neurotransmission in humans: A [11C] CUMI-101 PET challenge study - Selvaraj, S; Turkheimer, F; Rosso, L; Faulkner, P; Mouchlianitis, E; Roiser, J; McGuire, P; Cowen, P; Howes, O (2012)
Serotonin (5-HT) neurotransmission is implicated in cognitive and emotional processes and a number of neuropsychiatric disorders. The use of positron emission tomography (PET) to measure ligand displacement has allowed estimation of endogenous dopamine release in the human brain; however, applying this methodology to assess central 5-HT release has proved more challenging. The aim of this study was to assess the sensitivity of a highly selective 5-HT 1A partial agonist radioligand [11C] CUMI-101 to changes in endogenous 5-HT levels induced by an intravenous challenge with the selective 5-HT re-uptake inhibitor (SSRI), citalopram, in healthy human participants. We studied 15 healthy participants who underwent PET scanning in conjunction with [11C] CUMI-101 after receiving an intravenous infusion of citalopram 10 mg or placebo in a double-blind, crossover, randomized design. Regional estimates of binding potential (BPND) were obtained by calculating total volumes of distribution (V T) for presynaptic dorsal raphe nucleus (DRN) and postsynaptic cortical regions. Relative to placebo, citalopram infusion significantly increased [11C] CUMI-101 BP ND at postsynaptic 5-HT1A receptors in several cortical regions, but there was no change in binding at 5-HT1A autoreceptors in the DRN. Across the postsynaptic brain regions, citalopram treatment induced a mean 7% in [ 11C] CUMI-101 BPND (placebo 1.3 (0.2); citalopram 1.4 (0.2); paired t-test P0.003). The observed increase in postsynaptic [ 11C] CUMI-101 availability identified following acute citalopram administration could be attributable to a decrease in endogenous 5-HT availability in cortical terminal regions, consistent with preclinical animal studies, in which acute administration of SSRIs decreases DRN cell firing through activation of 5-HT1A autoreceptors to reduce 5-HT levels in postsynaptic regions. We conclude that [11C] CUMI-101 may be sensitive to changes in endogenous 5-HT release in humans. © 2012 Macmillan Publishers Limited.